Cycles of Beauty Culture: Ethnography of Beauty Clinics Commodification - Murlianti, Sri (Universitas Negeri Semarang, 2014)
Skin care is not a completely new in beauty treatments. Previously there have been other types of cultural industry which also adopted the medical science, such as cosmetic and beauty salon industries. But, skin care beauty clinic successfully introduces the services of beauty treatments which are considered the healthiest. This paper is a summary of the research on how beauty clinic quickly became a part of everyday life of its consumers. The research focused on Natasha Skin Care, a most popular beauty clinic in Indonesia at the moment. According to Richard Johnson, the process of a culture industry reaches the society through a communication that in form a pattern cyclic communications. The stages in the pattern are interconnected but slipped, each stage is affecting others but are not specified in an uncertain manner; between the producer of culture industry with its consumers. This study is a multidiscipline research using three methods of interpretation namely ethnography, discourses analysis, and social hermeneutic study.Klinik kecantikan bukanlah budaya yang benar-benar baru dalam perawatan kecantikan. Sebelumnya telah ada jenis industri budaya lain yang juga mengadopsi ilmu kedokteran, seperti industri kosmetik dan salon kecantikan. Namun klinik kecantikan sukses menyandang predikat sebagai jasa perawatan kecantikan yang dianggap paling sehat. Tulisan ini merupakan rigkasan penelitian tentang bagaimana klinik kecantikan begitu cepat menjadi bagian hidup sehari–hari masyarakat konsumennya. Fokus penelitian ini adalah Natasha Skin Care, sebuah klinik kecantikan paling popular di Indonesia saat ini. Menurut Richard Johson proses sebuah industri budaya sampai pada masyarakat konsumennya melalui komunikasi yang timpang, membentuk pola komunikasi siklik, saling terhubung namun penuh dengan keterpelesetan, saling mewarnai namun tidak menentukan secara pasti antara produsen industri budaya dengan masyarakat konsumennya. Penelitian ini ditempuh dengan kerja multidispliner, menggunakan setidaknya tiga metode interpretasi, yaitu etnografi, analisis wacana dan hermenuitik sosial.